2020
DOI: 10.3390/joitmc6040123
|View full text |Cite
|
Sign up to set email alerts
|

Innovations in Education—The Development of a New Pedagogical Technology of a Combinational Type, Focused on the Development of Personality of Students

Abstract: The paper considers the problem of adolescent and young students’ personalities’ development in the conditions of face-to-face and distance school learning. The scientific novelty of the study is the proposed classification of pedagogical technologies according to the degree of their novelty: modernized technology, combinational technology, progressive technology, pedagogical technology of the combinational type, the essence of which is shown in its title. A specific model of pedagogical technology of the comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
0
5
1
Order By: Relevance
“…The findings obtained in this study identify that if the teacher has high Knowledge Management, good Transformational leadership and a good personality, these three variables contribute to an increase in innovativeness. This study's findings differ from previous studies (Abdel Hadi et al, 2023;Fandos-Herrera et al, 2023;Lam et al, 2021a;Stock et al, 2016;Zhurakovskaya et al, 2020). Previous research found the strength of the relationship between innovation and knowledge management, transformational leadership, and personality, as evidenced by the analysis results.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…The findings obtained in this study identify that if the teacher has high Knowledge Management, good Transformational leadership and a good personality, these three variables contribute to an increase in innovativeness. This study's findings differ from previous studies (Abdel Hadi et al, 2023;Fandos-Herrera et al, 2023;Lam et al, 2021a;Stock et al, 2016;Zhurakovskaya et al, 2020). Previous research found the strength of the relationship between innovation and knowledge management, transformational leadership, and personality, as evidenced by the analysis results.…”
Section: Resultscontrasting
confidence: 99%
“…The problem regarding teacher innovation is an attraction for research (Sukmanasa et al, 2019). Research on innovation has also attracted researchers' attention (Gault, 2018;Ragazzi et al, 2012;Zhurakovskaya et al, 2020). However, have differences in variables and research findings.…”
Section: Introductionmentioning
confidence: 99%
“…Teenagers are capable of quickly learning and utilizing every development of technology and information [ 21 , 22 ]. Adolescents’ time is frequently spent using technology that is also developing rapidly [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Educational technology plays a crucial role in enhancing students' personality growth and motivation for learning. 16 Studies 17,18 have highlighted the significance of innovative education in improving the readiness for learning. The application of educational technology, along with changes and innovative approaches, directly impacts the activities of both professors and students.…”
Section: Introductionmentioning
confidence: 99%